Effect of homogenisation speed and centrifugation on particle size analysis of beef and the relationship with shear force. (September 2018) - Silva, Douglas R.G.; Holman, Benjamin W.B.; Kerr, Matthew J.; Morris, Stephen; Ramos, Eduardo M.; Hopkins, David L.
Abstract: This study aimed to investigate the effect of homogenisation speed and centrifugation on particle size (PS) evaluation, and examine its relationship with shear force. Beef Longissimus lumborum (LL) muscle portions were randomly assigned to different ageing periods (0, 3 or 5 weeks), and tested for PS and shear force. The PS analysis was conducted at different homogenisation speeds (11, 000, 16, 000 and 19, 000 rpm) with and without a centrifugation step prior to measurement. Samples homogenised at 11, 000 rpm and not centrifuged gave PS results significantly different at each ageing time as did samples homogenised at 19, 000 rpm and centrifuged. Overall samples homogenised at 11, 000 rpm produced the lowest coefficient of variation for PS results. There was a significant correlation between PS and shear force across the different homogeniser speeds and centrifugation statuses. It is concluded that best practice when measuring PS in beef includes a homogeniser speed of 11, 000 rpm with no centrifugation prior to measurement. Highlights: Samples homogenised at 11, 000 rpm gave the best PS outcome. 11, 000 rpm homogenisation speed had the lowest coefficient of variation. A significant relationship existed between PS and shear force.